Water in The Arab World : Management Perspectives and Innovations (World Bank, 2009)
This volume is intended to serve as a water handbook. It represents the collective knowledge about water resources management acquired over recent years, both within the World Bank water team and with counterparts working in the Arab countries of North Africa and the Middle East (MNA). The chapters offer a cornucopia of ideas and themes. Some chapters are based on background papers prepared for the 2007 'MNA development report on water.' Others draw on sector work prepared at the request of client countries. Yet others summarize observations based on study tours or other learning events sponsored by the World Bank. Upon reviewing this lodestone of embedded knowledge, the author realized that bringing together the observations and analyses could serve a useful purpose for public officials, other practitioners, academics, and students who are interested in learning more about the complexities of managing water resources management in one of the driest parts of the world.